2021
DOI: 10.1136/bmjopen-2020-048416
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of remdesivir in COVID-19 caused by SARS-CoV-2: a systematic review and meta-analysis

Abstract: ObjectivesEvaluation of remdesivir, an RNA polymerase inhibitor, for effectiveness in adults with COVID-19.Data sourcesElectronic search for eligible articles of PubMed, Cochrane Central and clinicaltrials.gov was performed on 20 September 2020.Participants and study eligibility criteriaOnly randomised controlled trials (RCTs) evaluating efficacy of remdesivir in COVID-19 were included for meta-analysis.InterventionsRemdesivir was compared with standard of care.Primary and secondary outcomesPrimary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 20 publications
1
37
0
8
Order By: Relevance
“…30 It was also affirmed that remdesivir is currently prescribed as one of the main treatments for COVID-19 in about 50 countries, 31 and the maximum recommended daily dose is approximately 250 mg/kg of solvent used to dissolve the drug. 32 The previous review stated that remdesivir is favorable in patients with severe COVID-19 compared to placebo, although the safety data on the use of remdesivir is currently sparse. 33 The systematic review and network meta-analysis conducted by Lai et al also showed that remdesivir helps to improve clinical outcomes of hospitalized patients and demonstrates a promising role in treating patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 It was also affirmed that remdesivir is currently prescribed as one of the main treatments for COVID-19 in about 50 countries, 31 and the maximum recommended daily dose is approximately 250 mg/kg of solvent used to dissolve the drug. 32 The previous review stated that remdesivir is favorable in patients with severe COVID-19 compared to placebo, although the safety data on the use of remdesivir is currently sparse. 33 The systematic review and network meta-analysis conducted by Lai et al also showed that remdesivir helps to improve clinical outcomes of hospitalized patients and demonstrates a promising role in treating patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 30 It was also affirmed that remdesivir is currently prescribed as one of the main treatments for COVID-19 in about 50 countries, 31 and the maximum recommended daily dose is approximately 250 mg/kg of solvent used to dissolve the drug. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Some of the strategies being used to control the viral spread of the disease are the recommended use of face masks, hand gloves, and sanitizers. While quite a number of vaccines are being developed to stimulate the production of antibodies against the virus, there are still concurrent investigations exploring the therapeutic potential of some anti-viral agents, including remdesivir [52,53]. As the search for new anti-SARS-CoV-2 drugs continues, the use of heterocyclic organic compounds in anti-viral drug development is essential as they have been reported to be efficacious against other major viral infections [31,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…An updated meta-analysis of existing trials, including ACTT1, SOLIDARITY and other additional trials performed by the SOLIDARITY group, also demonstrated no mortality benefit of remdesivir (RR 0.91, 95% CI 0.79-1.05) [13]. Interestingly, the results of an ACTT2 study suggest that if remdesivir is given in combination with the Janus kinase-inhibitor baricitinib, significant decreases in time to recovery are observed in hospitalized patients with SARS-CoV-2 [14].…”
Section: Anti-viral Agentsmentioning
confidence: 98%